COLLABORATIVE GOVERNANCE AS A MODEL FOR FULFILLING PLANTATION WORKERS’ VOTING RIGHTS IN THE 2024 ELECTION IN PELALAWAN REGENCY, RIAU PROVINCE - Yuri, Bobby J.; Asrinaldi, Asrinaldi; Zetra, Aidinil (Universitas Padjadjaran, 2025)
The low awareness among migrant workers of the need to exercise their voting rights is rarely highlighted. This research addresses how the General Elections Commission (KPU) and companies can realize the voting rights of these workers. One solution offered is the establishment of TPS in unique locations, namely within companies. This article views the successful establishment of TPS in these particular locations as an application of the collaborative governance concept. This article uses a qualitative research approach of the case study type. This research collected data through in-depth interviews with several sources from the KPU and Bawaslu of Pelalawan Regency, PT. Riau Andalan Pulp and Paper (PT. RAPP), labor unions, and other stakeholders. This article finds that the collaborative governance implemented by the Pelalawan Regency KPU and PT. RAPP to fulfill the political rights of workers follows several key stages. These stages reflect the process of collaborative governance, namely collaborative initiatives, the parties involved, the collaborative process, the collaborative result, and the collaborative impact. By adhering to the principles of collaborative governance, the Pelalawan Regency KPU and PT. RAPP have established a more effective and harmonious partnership, ultimately leading to better and more sustainable outcomes for all parties involved.